2015
DOI: 10.1080/01419870.2015.1081962
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising mosques? The role of service attendance for political participation of Turkish and Moroccan minorities in the Netherlands

Abstract: Religious service attendance has been identified as an important source of political participation among Christians and Muslims in the USA. In Europe, where religion is seen as a barrier rather than a bridge to Muslims' integration, the role of mosque attendance for the political participation of Muslims remains understudied. This study asks whether the politically mobilizing role of service attendance extends to Muslim minorities in Europe. We examine direct and indirect effects of the frequency of religious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…These civically mobilizing effects of mosques have also been confirmed by Fleischmann, Martinovic, and Böhm. (2016), who examined the effects of religious service attendance among Muslims of Moroccan and Turkish origin in the Netherlands.…”
Section: Synthesising Evidence: Relationship Between Islamic Religiossupporting
confidence: 72%
“…These civically mobilizing effects of mosques have also been confirmed by Fleischmann, Martinovic, and Böhm. (2016), who examined the effects of religious service attendance among Muslims of Moroccan and Turkish origin in the Netherlands.…”
Section: Synthesising Evidence: Relationship Between Islamic Religiossupporting
confidence: 72%
“…Thus, there is no reason to assume that the widely accepted tenet that citizens' involvement in non-political institutions and organizations can enhance political participation (Verba, Schlozman, and Brady 1995, 369) would not also apply to Muslim community organizations. This resonates with a number of studies that have found evidence for direct or indirect effects of Muslim community activism on political participation (Jamal 2005;McAndrew and Sobolewska 2015;Read 2015;Fleischmann, Martinovic, and Böhm 2016).…”
Section: Community Activism As a Gateway To Political Participationmentioning
confidence: 81%
“…McAndrew and Voas (2014) found that British Muslims with higher levels of subjective religiosity and communal religious practice were more likely to participate in a (mainstream) civil society organization and to become involved in politics or community affairs. In the Netherlands, Fleischmann, Martinovic, and Böhm (2016) demonstrate in their empirical study among Turkish and Moroccan Muslims that their participation in ethnic or ethno-religious community organizations correlates positively and significantly with their political trust, which, in turn, has significantly positive effects on political participation.…”
Section: Muslim Community Organizations: Promoting Civic and Politicamentioning
confidence: 99%
“…Yet, research on second-generation Muslim immigrants finds fewer negative and sometimes even positive associations between religiosity and integration outcomes such as education, employment, interethnic marriage, civic engagement, and gender egalitarianism (Carol and Schulz 2018;Fleischmann and Phalet 2012;Fleischmann, Martinovic and Böhm 2016;Maliepaard, Lubbers, and Gijsberts 2010;Maliepaard, Gijsberts, and Lubbers 2012;Ohlendorf, Koenig and Diehl 2017;Scheible and Fleischmann 2013). For example, Fleischmann and Phalet (2012) investigated second-generation Turkish immigrants in four European cities and found neither educational attainment, employment status nor interethnic marriage to be associated with immigrants' religiosity in Amsterdam, Brussels and Stockholm.…”
Section: Dimensions and Indicators Of Immigrant Integrationmentioning
confidence: 99%
“…Previous studies typically focused on a single or few selected integration outcomes, for instance egalitarian gender ideology (e.g. Scheible and Fleischmann 2013), educational attainment and employment status , political participation (Fleischmann, Martinovic, and Böhm 2016) or social integration (Maliepaard and Phalet 2012). The current study offers a more comprehensive test of the role of immigrant generation in the association between religiosity and the integration of Moroccan and Turkish immigrants in the Netherlands by including eight different indicators of immigrant integration, covering its structural, social, cultural, and psychological dimensions.…”
Section: Introductionmentioning
confidence: 99%